Fine-Scale Spatial Structure of Soil Microbial Communities in Burrows of a Keystone Rodent Following Mass Mortality - Kaufmann, Chadwick; Cassin-Sackett, Loren (Frontiers in Ecology and Evolution, 2021)
Soil microbial communities both reflect and influence biotic and abiotic processes occurring at or near the soil surface. Ecosystem engineers that physically alter the soil surface, such as burrowing ground squirrels, are expected to influence the distribution of soil microbial communities. Black-tailed prairie dogs (Cynomys ludovicianus) construct complex burrows in which activities such as nesting, defecating and dying are partitioned spatially into different chambers. Prairie dogs also experience large-scale die-offs due to sylvatic plague, caused by the bacterium Yersinia pestis, which lead to mass mortality events with potential repercussions on microbial communities. We used 16S sequencing to examine microbial communities in soil that was excavated by prairie dogs from different burrow locations, and surface soil that was used in the construction of burrow entrances, in populations that experienced plague die-offs. Following the QIIME2 pipeline, we assessed microbial diversity at several taxonomic levels among burrow regions. To do so, we computed community similarity metrics (Bray-Curtis, Jaccard, and weighted and unweighted Unifrac) among samples and community diversity indexes (Shannon and Faith Phylogenetic diversity indexes) within each sample. Microbial communities differed across burrow regions, and several taxa exhibited spatial variation in relative abundance. Microbial ecological diversity (Shannon index) was highest in soil recently excavated from within burrows and soils associated with dead animals, and was lowest in soils associated with scat. Phylogenetic diversity varied only marginally within burrows, but the trends paralleled those for Shannon diversity. Yersinia was detected in four samples from one colony, marking the first time the genus has been sampled from soil on prairie dog colonies. The presence of Yersinia was a significant predictor of 5 bacterial families and 8 microbial genera, most of which were rare taxa found in higher abundance in the presence of Yersinia, and one of which, Dictystelium, has been proposed as an enzootic reservoir of Y. pestis. This study demonstrates that mammalian modifications to soil structure by physical alterations and by mass mortality can influence the distribution and diversity of microbial communities.